Distribution, deposition and impact of tailing disposal on the seafloor in Ranfjorden, northern Norway - Haugen, Anders Eirik (UiT Norges arktiske universitet, 2018)
This study is conducted in Ranfjorden in northern Norway with the goal of gaining a better understanding of the interaction between natural and anthropologic sediments within the fjord. Ranfjorden is of interest due to the fact that it has experienced extensive anthropologic impacts over the last 100 years with the submarine tailings placement (STP) of mine tailings ongoing. The analysis of this study uses the combination of 6 Niemistö sediment cores, 10 sediment grabs, swath bathymetry and high resolution seismic data to identify natural and anthropologic sediments and determine how their distribution has impacted the fjord. The sediment cores were analyzed to determine their physical properties including magnetic susceptibility, geochemical element measurements, grainsize analysis and lithological analysis. The resulting data showed mine tailings sediments to be characterized by a darker red color, higher magnetic susceptibility and Fe/Sum values with low fluctuations in Fe/Sum values. The more natural fjord sediments are characterized by gray colors, lower magnetic susceptibility and Fe/Sum values with higher fluctuations in Fe/Sum values. Using these identifying traits it was shown that the majority of the inner fjord has experience varied levels of impact from the mine tailings, with all the sediment cores showing traces of mine tailings. The mean grainsize of the sampled mine tailings was shown to vary from fine sand to very fine silt. The fjord slopes surrounding the mine tailings discharge points at the head of the fjord appeared in the swath bathymetry to have experienced extensive erosion in the form of mass movement and gravity flows. This is attributed to the accumulation of finer mine tailings along these slopes due to back flowing estuarine circulation currents. These currents accompanied by the river-induced halocline appear to capture rising sediment plumes in the water column and concentrate them in those areas. The eroded sediments from those slopes combined with coarser mine tailings are ...